Structure and chemical nature of intercellular protuberances in Dennstaedtiaceae rhizomes (Polypodiopsida) (Acta Scientiarum. Biological Sciences, 2023)
Intercellular protuberances (IPs) are projections on the cell surface and have been reported for families of ferns, Gymnosperms, and Angiosperms. Data on the type, chemical composition, and distribution of these structures among vascular plants are still scarce. Here, we investigate the occurrence, distribution, type of IPs among species of eight Dennstaedtiaceae genera and verify the taxonomic significance of these protuberances in the family. Rhizomes of 23 species of Dennstaedtiaceae from field and herbaria collections were analyzed by light microscopy and scanning electron microscopy. Histochemical tests were performed to identify the main classes of IPs chemical compounds. Two types of IPs were observed in Dennstaedtiaceae species: strand and filament types. They were observed in the intercellular spaces of the parenchyma in the cortex and pith regions. Overall, protuberances are irregularly shaped, with angustate or spheroidal apices. Their polysaccharide nature and pectic constitution were confirmed by histochemical tests. Concerning Pteridium arachnoideum (Kaulf.) Maxon subsp. arachnoideum, IPs have confirmed phenolic composition. Evidence indicates that IPs in Dennstaedtiaceae originate from the fragmentation of the middle lamella and that they have a structural function as well as protection against pathogens. In lateral-line aerenchyma, the occurrence of filament-type IPs may be related to the larger intercellular spacing in the cortex region, providing greater mechanical resistance. We have expanded the data on the occurrence of IPs in the Dennstaedtiaceae, which appear to be notable characters for the family. Moreover, the data presented herein confirmed the polysaccharide and pectic nature of these structures. However, we were unable to find links between IPs and taxonomy and evolution of the Dennstaedtiaceae. On the other hand, different IPs types were identified between the clades Dennstaedtioideae (strand-type IPs) and Hypolepidoideae (filament-type IPs, with exceptions).